A Multi-agent System Approach for Management of Industrial IoT Devices in Manufacturing Processes - Cagnin, Renato L. [UNESP]; Guilherme, Ivan R. [UNESP]; Queiroz, Jonas [UNESP]; Paulo, Bruno [UNESP]; Neto, Marcilio F.O. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2018)
Industry 4.0 is the new industrial revolution that uses technologies to enable communication and interaction between devices. In this new environment, applications are designed to ensure concepts like connection, data sharing, accessibility and process automation. In a process automation context, applications must coordinate and manage the execution of different tasks performed by autonomous devices. Aiming to support the development of such applications this paper presents an architecture for the development of an approach based on Multi-agent systems (MAS), Service-Oriented Architecture and Semantic Web technologies. The architecture uses MAS organizational approach and ontologies to ensure and automate the devices management in IoT environments. A case study in a simulated industrial environment aiming the manufacturing of metallic components is presented in order to show the proposal features and feasibility.
Keywords: Internet of Things; Multi-Agent Systems; Semantic Web Technologies; Service Oriented Architecture